Mechanistic insight into the mode of inhibition of dietary flavonoids; targeting macrophage migration inhibitory factor - Siddiqui, Ali Raza; Mushtaq, Mamona; Sardar, Madiha; Atta, Lubna; Nur-e-Alam, Mohammad; Ahmad, Aftab; Ul-Haq, Zaheer (Frontiers in Molecular Biosciences, 2024)
The Macrophage Migration Inhibitory Factor (MIF), a key pro-inflammatory mediator, is responsible for modulating immune responses. An array of inflammatory and autoimmune diseases have been linked to the dysregulated activity of MIF. The significance in physiological as well as pathophysiological phenomena underscores the potential of MIF as an attractive target with pharmacological relevance. Extensive research in the past has uncovered a number of inhibitors, while ISO-1, or (S, R)-3-(4-hydroxyphenyl)-4,5-dihydro-5-isoxazole acetic acid methyl ester, has been recognized as a benchmark standard so far. Recent work by Yang and coworkers identified five promising dietary flavonoids, with superior activity compared to the standard ISO-1. Nevertheless, the exact atomic-level inhibitory mechanism is still elusive. To improve dynamic research and rigorously characterize and compare molecular signatures of MIF complexes with ISO-1 and flavonoids, principal component analysis (PCA) was linked with molecular dynamics (MD) simulations and binding free energy calculations. The results suggest that these small molecule inhibitors could modify MIF activity by blocking the tautomerase site, thereby disrupting intrinsic dynamics in particular functional areas. The stability matrices revealed the average deviation values ranging from 0.27-0.32 nm while the residue level fluctuations indicated that binding of the selected flavonoids confer enhanced stability relative to the ISO-1. Furthermore, the gyration values extracted from the simulated trajectories were found in the range of 1.80-1.83 nm. Although all of the tested flavonoids demonstrated remarkable results, particularly Morin and Amentoflavone, which are potent inhibitors, exhibited a good correlation with biological activity. The PCA results in particular featured relatively less variance and constricted conformational landscape than others. The stable ensembles and reduced variation in turns might be possible reasons for their outstanding performance as documented previously. The results from the present exploration provide a comprehensive understanding of the molecular complexes formed by flavonoids and MIF, shedding light on their potential roles and impacts. Future studies on MIF inhibitors may benefit from the knowledge gathered from this investigation.